Analisis dan Perancangan Sistem Absensi Karyawan Berbasis Website di SMP Santo Leo - Bintang Dwinanto Prakoso; Agus Budiyantara (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze and design a website-based employee attendance system at SMP Santo Leo as a solution to the weaknesses of the manual attendance system which is prone to recording errors, data loss, and inefficiencies in recapitulation and attendance monitoring. The design method uses the Unified Modeling Language (UML) approach to systematically visualize system needs and workflows. The system developed has the main features in the form of recording attendance in and out of the house, applying for permits, and making automatic attendance reports. The system test is carried out using the User Acceptance Test (UAT) method based on five aspects: functionality, ease of use, suitability, system performance, and interface display. The test results show that the user satisfaction rate is in the range of 85% to 92%, which is categorized as "Excellent". The evaluation concluded that the system was in accordance with the design, ran stable, was easy to use without special training, and was able to improve efficiency and accuracy in employee attendance management. This system is declared feasible to be implemented operationally within the Santo Leo Junior High School environment and has the potential to support managerial decision-making based on attendance data. The study also recommends further development through integration with payroll systems and automated notification features to improve the functionality and usability of the system.